The Influence of Environmental, Social, Governance (ESG) and Green Innovation on Company Business Performance - Ramadhan, Ahmad; Widiastuty, Erna (Journal of Financial and Behavioural Accounting, 2023)
The research aims to provide empirical evidence on the relationship of ESG and green innovation to company's business performance. The independent sample of this research is ESG was measuring ESG score. Dependent variables green innovation were measures using innovation of green product and innovation of green process. Sampling used in this research is purposive sampling technique. The sample of this research consisted of 66 manufacturing companies from 2016 to 2021. The data collected was analyzed using panel data regression analysis. This result shows that ESG positively influence business performance proxied by Tobin's Q and ROA unsupported. Green Innovation, which is proxied by green product innovation on the company's business performance, shows mixed results. Where green product innovation positively influence the company's business performance proxied by ROA. Conversely, green product innovation does not influence company's business performance proxied by Tobin's Q. Meanwhile, Green Innovation proxied by Green Process innovation effect on the company's business performance is not supported. Thus, it can be seen that ESG has not become a concern for investors in Indonesia, as evidenced by the limited number of public companies that disclose ESG scores. Green Innovation which is proxied by green product innovation and green process innovation shows mixed results which shows that customers are also considering purchasing products from companies whose innovations produce environmentally friendly products